Application of Brakes on Cranes in River Ports - Rakúsová, Danka; Kopecký, Ivan; Lipták, Peter (Manufacturing Technology Journal, 2017)
In the last decades, advanced brake technology in the port sector follows the global productivity developments of the international maritime trade. Container vessels are getting bigger and bigger and the ship to shore cranes is getting consistently higher. But service, emergency or storm brakes cannot be getting bigger and bigger to meet these increasing demands. Throughout history, innovations and advancements in technology have made industry better through automation and increased efficiency. No matter how advanced industry becomes, the need for emergency duty stopping brakes will not go out of style because there are always circumstances that require mechanical brakes to do the job. Brakes will invariably insure against those rare, yet potentially catastrophic events that even modern technology cannot defend against.
Keywords: brakes; disc; regulated braking; emergency brake; braking torque